Pattern of Diabetes Mellitus Complications and Co-morbidities in Ughelli North Local Government Area, Delta State, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Diabetes mellitus (DM) is a metabolic disorder associated with reduced life expectancy, microvascular complications, increased risk of macrovascular complications and diminished quality of life.Aims:To assess the pattern of DM complications and co morbidities in Ughelli North Local Government Area, Delta State, Nigeria.Settings and Design:This was a 7 year retrospective study conducted in General Hospital Ughelli Delta State, Nigeria.Materials and Methods:A designed pro forma was used to collect the basic information from patients who presented themselves from the year 2010–2017.Statistical analysis used:The collected data were entered into the computer and analysed using the SPSS software version 20.0. The data were presented in simple percentages and charts, whereas Pearson correlation was used to test for correlation among variables of interest at the level of significance (P< 0.05).Results:The total number of patients was 53,421, of which 19,391 (36.29%) were females, 18,559 (34.75%) males and 15,435 (28.95%) children. The overall prevalence of diabetes was 25.46% with the prevalence among males 46.63% and females 53.37% at (P= 0.000), respectively. The pattern of diabetes complications was kidney failure (27.87%), heart attack (27.27%), erectile dysfunctions (21.0%) and cardiovascular diseases (10.0%). Prevalent diabetes comorbidity recorded were hypertension (54.0%), peptic ulcer (7.0%) and asthma (4.0%).Conclusion:The present study showed the prevalence of DM and the presence of complications among the patients.